Boat accident on the Danube in 1868 (Academic Journal of Internal Affairs, 2020)
The first accident of river steamboats in Hungary occurred in 1868 on the Danube. The significantly larger Karl Ludwig crashed into the steamship Slavonia on the border of two counties, resulting in the death of two passengers. In national criminal law the rules and regulations necessary for determining criminal liability in such a case did not exist at that time. In its final decision of 1873, the court acquitted the prosecuted ship captains.
Keywords: Danube; steamboat; shipping rules; boat crash